Pinitol Improves Diabetic Foot Ulcers in Streptozotocin-Induced Diabetes Rats Through Upregulation of Nrf2/HO-1 Signaling - Jinsick Kim; Min Young Go; Chae Young Jeon; Jung Un Shin; Mujun Kim; Hye Won Lim; Dong Wook Shin (Antioxidants)
Diabetic foot ulcers represent a severe complication of diabetes, often resulting in amputation and high mortality rates. Currently, there are no treatments for diabetic foot ulcers other than antibiotics and dressings. In this study, we evaluated the wound-healing effects of an antidiabetic agent pinitol in lipopolysaccharide (LPS)-damaged human dermal fibroblasts (HDFs) and streptozotocin (STZ)-induced diabetic rat models with a foot wound. Our findings indicated that pinitol enhanced cell migration, proliferation, and wound healing by activating Nrf2, thereby mitigating oxidative stress and inflammatory responses at the wound site. Additionally, pinitol restored mitochondrial energy metabolism, decreased matrix metalloproteinase (MMP) activity, and increased collagen deposition. Furthermore, pinitol facilitated angiogenesis, contributing to improved wound healing. Taken together, these findings suggest that pinitol could be a promising therapeutic agent for the treatment of diabetic foot ulcers.